The State of the HR Profession - Ulrich, Dave; Younger, Jon; Brockbank, Wayne; Ulrich, Michael D. (Human Resource Management, 2013)
AbstractWe want to create a new narrative about the human resource (HR) profession. HR professionals have often been plagued with self‐doubts, repeatedly re‐exploring HR's role, value, and competencies. If HR is to fully (and finally) become a profession, these self‐doubts need to be replaced with informed insights. These informed insights should be based more on global data than personal perceptions so that the emerging narrative for the HR profession has both substance and meaning.